Jejak Historis Peran Da’i Selaku Tokoh Agama di Masa Covid-19 Pada Masyarakat Cipinang Besar Selatan, Jakarta Timur - Pipin Yosepin; Muhadi; Elis Maslihah (Program Studi Komunikasi dan Penyiaran Islam, 2024)
This writing describes the historical traces of the role of preachers as religious leaders in preventing the Covid-19 virus in the Cipinang Besar Selatan community, East Jakarta.This research uses a qualitative method with a phenemonological approach. Data collection techniques were obtained from observation, documentation and field interviews with 3 preachers, 2 community members. The occurrence of the Covid -19 pandemic in 2020-2021, some community members are still ignorant of the transmission of the virus. Hoax information on social media creates confusion in the community. The high mortality rate makes psychic disturbances and panic buying of medical devices that have soared in need. Social distancing and lockdown policies make the laws of worship change and religious institutions demand the role of preachers as religious leaders. The role of preachers during the covid-19 pandemic is: 1) as a provider of reliable information to citizens providing information to the public about the importance of maintaining health and using health protocols. 2) Da’i has a role in conveying MUI fatwas related to how to worship and guide the community. 3) Da’i also acts as a protector of the soul, especially for people who are experiencing family loss. Factors that support the role of preachers are the role of residents in Rw 04, Cipinang Besar Selatan urban village who cooperate in spraying disinfectants on mosques, schools, mushollas and residents' homes. The inhibiting factors are the ignorance of some people in Cipinang Besar Selatan who consider the transmission of the Covid-19 virus light and hoax information from social media. Da’i as a religious figure during the Covid-19 pandemic became the spearhead of information facilities for the prevention of the Covid-19 virus in the community in Cipinang Besar Selatan, East Jakarta. Da’i has a historical footprint and is a role model in the community in inviting people to be more vigilant, especially in providing positive information and still using health protocols in worshiping at the mosque during the Covid-19 pandemic.